Assessing Residual Bias in Estimating Influenza Vaccine Effectiveness: Comparison of High-dose Versus Standard-dose Vaccines. Issue 1 (January 2019) - Butler, Anne M.; Layton, J. Bradley; Krueger, Whitney S.; Kshirsagar, Abhijit V.; McGrath, Leah J.
Abstract : Background: Estimating influenza vaccine effectiveness using an unvaccinated comparison group may result in biased effect estimates. Objectives: To explore the reduction of confounding bias in an active comparison of high-dose versus standard-dose influenza vaccines, as compared with vaccinated versus unvaccinated comparisons. Methods: Using Medicare data from the United States end-stage renal disease program (2009–2013), we compared the risk of all-cause mortality among recipients of high-dose vaccine (HDV) versus standard-dose vaccine (SDV), HDV versus no vaccine, and SDV versus no vaccine. To quantify confounding bias, analyses were restricted to the preinfluenza season, when the protective effect of vaccination should not yet be observed. We estimated the standardized mortality ratio-weighted cumulative incidence functions using Kaplan-Meier methods and calculated risk ratios (RRs) and risk differences between groups. Results: Among 350, 921 eligible patients contributing 825, 642 unique patient preinfluenza seasons, 0.8% received HDV, 70.5% received SDV, and 28.7% remained unvaccinated. Comparisons with unvaccinated patients yielded spurious decreases in mortality risk during the preinfluenza period, for HDV versus none [RR, 0.60; 95% confidence interval (CI), 0.51–0.70)] and SDV versus none (RR, 0.72; 95% CI, 0.70–0.75). The effect estimate was attenuated in the HDV versus SDV comparison (RR, 0.89; 95% CI, 0.77–1.03). Estimates on the absolute scale followed a similar pattern. Conclusions: The HDV versus SDV comparison yielded less-biased estimates of the all-cause mortality before influenza season compared to those with nonuser comparison groups. Vaccine effectiveness and safety researchers should consider the active comparator design to reduce bias due to differences in underlying health status between vaccinated and unvaccinated individuals. Abstract : Supplemental Digital Content is available in the text.